2015
DOI: 10.1097/jcn.0000000000000142
|View full text |Cite
|
Sign up to set email alerts
|

Gender- and Age-Specific Prevalence of Metabolic Syndrome Among Korean Adults

Abstract: Metabolic syndrome is prevalent in a representative sample of Korean adults, with gender- and age-specific patterns. These results are helpful in identification of vulnerable subgroups at high risk for MetS, providing a basis for promotion of cardiovascular health and risk management of MetS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 32 publications
(53 reference statements)
8
25
0
Order By: Relevance
“…Studies have shown that MetS prevalence differs according to gender, age, and country [27, 14, 15]. Using the National Cholesterol Education Program’s (NCEP) definition of MetS, age-adjusted prevalence of MetS among adults over 20 years of age is estimated at 31.3 % in Korea [4], which is similar to estimates in the US [2].…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…Studies have shown that MetS prevalence differs according to gender, age, and country [27, 14, 15]. Using the National Cholesterol Education Program’s (NCEP) definition of MetS, age-adjusted prevalence of MetS among adults over 20 years of age is estimated at 31.3 % in Korea [4], which is similar to estimates in the US [2].…”
Section: Introductionmentioning
confidence: 70%
“…Using the National Cholesterol Education Program’s (NCEP) definition of MetS, age-adjusted prevalence of MetS among adults over 20 years of age is estimated at 31.3 % in Korea [4], which is similar to estimates in the US [2]. The prevalence of MetS has been increasing [4, 14] over the last decades; this increase has been attributed to an increased incidence of dyslipidemia and abdominal obesity in Korean adults [4, 14]. Among old adults, MetS prevalence has been reported to vary from 20 to 60 %, with higher prevalence in females than males in several studies [3, 57, 15].…”
Section: Introductionmentioning
confidence: 98%
“…Other studies conducted in Iran and other parts of the world reported a higher prevalence for MS. The prevalence of this disorder among adults was 38.5% in the United States [9], 27.8% in Spain [32], 21.1% in France [10], 25.9% in Norway [33], 54.8% in Mexico [11], 35.73% in Morocco [2], 30% in Tanzania [34], 25% in Korea [35], 21.3 -39% in China [12,13], 40-50% in India [36], 21% in Saudi Arabia [14], 36.3% in Jordan [37], 33.5% in Turkey [15], and 21.9% -32% in different regions of Iran [16][17][18][19][20][21][22][23]. Possible reasons for this difference and lower prevalence of MS, are racial and regional differences, age differences between studies, and the use of different definitions for MS.…”
Section: Discussionmentioning
confidence: 99%
“…Sex-specific [52] risk predictors should be considered in primary prevention for incidence of MetS in workplaces. Each component of MetS intervention has independent goals to be achieved, while no single effective pharmacological treatment simultaneously affecting all components of MetS equally has yet been found.…”
Section: Metabolic Syndrome Component Count and Shift Work O R I G I mentioning
confidence: 99%